Review Of The Scoping: The Value Of Diversity Management In Preventing Deviant Behavior At Work - Elfia Nora; Sopiah Sopiah (FKIP, Universitas Palangka Raya, 2023)
Reviews of the literature on diversity management and workplace misconduct are still incredibly uncommon. Given the requirement for appropriate handling to stop irregular conduct at work (organizations; companies, government institutions, MSMEs). This scoping review's objective is to summarize the literature on the value of diversity management in avoiding workplace deviance. The scoping study adheres to the Arksey and O'Malley Steps. (2005). The scoping review used has 5 steps, including identifying research topics, finding pertinent studies, Specifically, (1) formulating research questions, (2) locating pertinent studies, (3) choosing studies, (4) outlining data, and (5) gathering, describing, and disclosing findings. Over 11 years, this research was reviewed using 3 electronic databases: Taylor dan Francis, Wiley dan Emerald. (2013-2023). Corruption, the giving of gifts or bribes, and gossip are among the categories of deviant behavior in the workplace that were identified, and all of these categories have the potential to negatively impact organizational performance, according to the findings of the scoping review. Gender, race, and culture are three types of diversity that are particularly susceptible to the issue of aberrant behavior in the workplace. Therefore, management must provide support and focus, particularly to human resource managers who are responsible for managing diversity in the workplace.